Platform economies: Beyond the North-South divide - Janet Roitman (Finance and Society, 2023)
Platform economies are depicted as the foundation for a new era of economic production. This transpires through the incorporation of digital technologies and algorithmic operations into the heart of economic and financial practices. However, different assumptions are made about the effects of digital platforms depending on geographical location. While digital platforms are approached as inherent to processes of financialization globally, they are reduced to processes of financial inclusion when referencing the "Global South". Analyses of financialization as a one-way-vector - Global North to Global South - overlook the variability, the limits, and responses to financialization. In contrast, a focus on market devices illustrates the specificities of value creation. An example of this is "the float", a form of financial value generated by mobile telecommunication operators, mobile money issuers, and commercial banks in Africa. Through this lens, we see instances of both value subjugation and autonomization, evidence that the fault lines of value production generated by ambiguous market devices are obscured by the Global North/Global South frame.
Keywords: 300; financialization; Global South; mobile money; Platform economies; remittances; value creation